2021
DOI: 10.3389/fneur.2021.705221
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Edema in Subacute Lesion Progression After Treatment of Acute Ischemic Stroke

Abstract: Background: Ischemic lesions commonly continue to progress even days after treatment, and this lesion growth is associated with unfavorable functional outcome in acute ischemic stroke patients. The aim of this study is to elucidate the role of edema in subacute lesion progression and its influence on unfavorable functional outcome by quantifying net water uptake.Methods: We included all 187 patients from the MR CLEAN trial who had high quality follow-up non-contrast CT at 24 h and 1 week. Using a CT densitomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…This study provides a new way to assess the RPBE (an increase of more than two points in cerebral edema mass effect within 24 h). The occurrence of RPBE observed in this study (26.2%) is comparable with the 24 h net water uptake observed in previous research (20.6-22.0%) (25,26). Although RPBE is a semi-quantitative assessment, it shows the predictive value for poor early clinical outcomes (Table 2), which is consistent with previous studies (7,8,27).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study provides a new way to assess the RPBE (an increase of more than two points in cerebral edema mass effect within 24 h). The occurrence of RPBE observed in this study (26.2%) is comparable with the 24 h net water uptake observed in previous research (20.6-22.0%) (25,26). Although RPBE is a semi-quantitative assessment, it shows the predictive value for poor early clinical outcomes (Table 2), which is consistent with previous studies (7,8,27).…”
Section: Discussionsupporting
confidence: 92%
“…Animal experiments have shown that rapidly progressing cerebral edema may occur after LVO, and increased BBB permeability was observed 20–155 min after MCA occlusion ( 29 ). A recent study reported that a larger edema volume within 24 h was associated with more edema and lesion progression ( 25 ). The mismatch ratio is the ratio of the penumbra volume to the infarct core volume, combining the infarct core with the mismatched volume.…”
Section: Discussionmentioning
confidence: 99%
“…This practice could have affected the accuracy of our FIV assessments because it is known that edema affects the FIV on NCCT after stroke, and it can be challenging to distinguish edema from infarcted tissue on NCCT. 39 However, the FIVs were not different for patients who received a median 24-hour followup DWI versus patients with 24-hour follow-up NCCT. In addition, it has been demonstrated that FIV assessed on 24-hour NCCT is equally strongly associated with functional outcome as the FIV measured on 1-week NCCT, regardless of the fact that infarct growth between 24-hour and 1-week imaging is common.…”
Section: Discussionmentioning
confidence: 85%
“…13 In addition, in these studies, true lesion growth was not distinguished from edema, although the latter may account for up to one-third of the lesion volume. 3,4,23 The use of a nonlinear coregistered MRI approach may limit this bias.…”
Section: Discussionmentioning
confidence: 99%